- Tinjauan terhadap penyelesaian perselisihan oleh para pihak pada pengadilan hubungan industrial pekanbaru : - - Muhammad Andika Rizqi; Yoga Pamungkas (Reformasi Hukum Trisakti, 2023)
In the settlement of industrial relations conflict disputes, Law Number 2 of 2004 regarding the Industrial Relations Court requires that a non-litigation settlement is an obligation that needs to be fulfilled first by the parties to the dispute. One of them is Bipartite Negotiation which is a formal requirement in resolving Industrial Relations Disputes conflicts. There are times when the process that the litigants go through is not in accordance with the applicable laws and regulations, such as the settlement process that the parties go through in decision Number: 40/Pdt.Sus-PHI/2020/PN Pbr. So the main problem is whether the procedure for resolving industrial relations conflicts between Sucipto Pardede and PT. Artha Prima Finance in the decision of the Industrial Relations Court is in accordance with the regulations of Law Number 2 of 2004 concerning Industrial Relations Disputes and Laws in the field of employment? And what are the legal consequences for the parties after the issuance of decision Number: 40/Pdt.Sus-PHI/2020/PN Pbr? To answer this problem, a normative juridical study was carried out on decision number 40/Pdt.Sus-PHI/2020/PN Pbr and with a descriptive nature